The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations VERMIN THE FLY IS A DANGER The fly, voyaging from filth to food, from the street to the baby's milk, is a danger. Wire gauze should screen the larder window. Meat, milk, etc., should be kept under fly-proof covers. Leave no refuse in the sink or remains of food lying about. Keep the dustbin dry and covered. No manure or refuse heap should be allowed near the kitchen door. Absolute cleanliness is the surest way of guarding against flies. Buy only from shops where this rule is enforced. [illustration] Flies are a menace to health. IF YOU FEAR THE WORST Vermin are seldom present in new houses. If you suspect their presence in your old home, ask the Sanitary Inspector to disinfect your belongings when you move. Be very careful of second-hand furniture. It is often infested with bugs. Cleanliness is your greatest safeguard against pests. FOR FLEAS Simple cleanliness is the best way of getting rid of fleas. Wash all over daily, have clean clothes as often as possible, and boil cotton and linen bed clothes and body linen for at least five minutes. Blankets should be scanned carefully if there is any reason to suspcct the presence of fleas. BLACKBEETLES AND COCKROACHES Extreme cleanliness is a weapon against these pests. Make sure the larder is proof against them and leave no food about. If you have a plague of beetles, consult the Sanitary Inspector. [illustration] 20 177/5/8/2